The Challenges of French Studies at Secondary School Level in Nigeria - Akintoye, Festus Ayodimeji (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
A well structured educational system is undeniably a formidable key to a nation’s development and survival in all spheres of life. Thus, every nation, via its ministry of Education is expected to give equal status and value to all subjects that are being offered at all strata of education. This is because every educated individual should be able to give back to the society positively through the training acquired. Therefore, this paper sets out, to discuss the challenges of French Language Studies in Nigeria at the Secondary School level. It shall go about this by explaining what language education means as well as presenting succinctly the history of French Language in Nigeria. The paper further discusses the challenges that teaching and learning French Language pose to French teacher and learner of the language in Nigeria Secondary school education in Nigeria is an educational stage to be attended by students after primary school education and before tertiary institution. This is a period for youth direction on subject specialization, most especially at the senior secondary level, leading to issue of professionalization, based on subject compartmentalization and choice of higher institution.